Production method of carbon nano-tube aqueous dispersion

JP2025035319APending Publication Date: 2025-03-13HOKUETSU CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023142289
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0014】 本発明に係るカーボンナノチューブ水分散液の製造方法によれば、カーボンナノチューブと、水と、カーボンナノチューブを水に分散させる分散剤と、を含む混合液を作製する工程と、湿式微粒化装置を用いて、混合液を分散させる工程と、を含み、混合液を分散させる工程では、混合液を、湿式微粒化装置のノズルから噴射させて、セラミック製または金属製の被衝突部材に衝突させるため、カーボンナノチューブの分散性が良いカーボンナノチューブ水分散液を製造できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035319000001_ABST
    Figure 2025035319000001_ABST
Patent Text Reader

Abstract

To provide a production method of a carbon nano-tube aqueous dispersion with excellent dispersibility.SOLUTION: A production method of a carbon nano-tube aqueous dispersion related to the invention comprises: a step of forming a mixture containing carbon nano-tubes, water, and a dispersant to disperse the carbon nano-tubes in water; and a step of dispersing the carbon nano-tubes contained in the mixture by using a wet type atomization apparatus. In the step of dispersing the carbon nano-tubes, the mixture is injected from a nozzle of the wet type atomization apparatus and made to collide with a ceramic or metallic collision member.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an aqueous dispersion of carbon nanotubes. [Background technology]

[0002] Carbon nanotubes have a structure similar to a uniform, flat graphene sheet rolled into a cylindrical shape. Due to this unique structure, carbon nanotubes have a variety of properties and are expected to be used in a wide range of fields.

[0003] Carbon nanotubes have a tendency to aggregate with each other, so it is difficult to disperse them uniformly in water. For example, Patent Document 1 describes a method in which carbon nanotubes, carboxymethyl cellulose, and water are mixed to prepare a mixed liquid, and the mixed liquids are collided with each other by an underwater head-on collision method to disperse the carbon nanotubes. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2021 / 065432 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of some aspects of the present invention is to provide a method for producing an aqueous dispersion of carbon nanotubes with good dispersibility. [Means for solving the problem]

[0006] One aspect of the method for producing a carbon nanotube aqueous dispersion according to the present invention is to A step of preparing a mixed liquid including carbon nanotubes, water, and a dispersant for dispersing the carbon nanotubes in the water; dispersing the carbon nanotubes contained in the mixture using a wet atomization device; Including, In the step of dispersing the carbon nanotubes, the mixture is sprayed from a nozzle of the wet-type atomization device and made to collide with a ceramic or metallic collision target member.

[0007] In one embodiment of the method for producing a carbon nanotube aqueous dispersion, The impacted member may be a ceramic ball.

[0008] In one embodiment of the method for producing a carbon nanotube aqueous dispersion, The dispersant may be carboxymethylcellulose or a salt thereof, or a polymer containing repeat units derived from acrylic acid.

[0009] In one embodiment of the method for producing a carbon nanotube aqueous dispersion, The dispersant may be sodium carboxymethylcellulose.

[0010] In one embodiment of the method for producing a carbon nanotube aqueous dispersion, The dispersant may be polyacrylic acid.

[0011] In one embodiment of the method for producing a carbon nanotube aqueous dispersion, The content of the carbon nanotubes in the mixture is 2.0% by mass or more. Good too.

[0012] In one embodiment of the method for producing a carbon nanotube aqueous dispersion, The content of the carbon nanotubes in the mixed liquid may be 3.0% by mass or more.

[0013] In one embodiment of the method for producing a carbon nanotube aqueous dispersion, The content of the carbon nanotubes in the mixed liquid may be 3.5% by mass or more. Effect of the Invention

[0014] The method for producing a carbon nanotube aqueous dispersion according to the present invention includes the steps of preparing a mixed liquid containing carbon nanotubes, water, and a dispersant for dispersing the carbon nanotubes in the water, and dispersing the mixed liquid using a wet atomization device. In the step of dispersing the mixed liquid, the mixed liquid is sprayed from a nozzle of the wet atomization device and collided with a ceramic or metallic collision target member, thereby producing a carbon nanotube aqueous dispersion with good dispersibility of carbon nanotubes. [Brief description of the drawings]

[0015] [Figure 1] 3 is a flowchart for explaining a method for producing a carbon nanotube aqueous dispersion according to the present embodiment. [Diagram 2] FIG. 2 is a cross-sectional view showing a schematic diagram of a wet-type atomization apparatus used in the method for producing an aqueous carbon nanotube dispersion according to the present embodiment. [Diagram 3] 1 is a table showing the preparation conditions and experimental results of carbon nanotube aqueous dispersions of Examples 1 to 10 and Comparative Examples 1 to 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Preferred embodiments of the present invention will be described in detail below with reference to the drawings. Note that the embodiments described below do not unduly limit the contents of the present invention described in the claims. In addition, not all of the configurations described below are necessarily essential components of the present invention.

[0017] 1. Method for producing carbon nanotube aqueous dispersion First, the method for producing a carbon nanotube aqueous dispersion according to the present embodiment will be described with reference to the drawings. Fig. 1 is a flow chart for explaining the method for producing a carbon nanotube aqueous dispersion according to the present embodiment.

[0018] The method for producing a carbon nanotube aqueous dispersion according to this embodiment includes a mixed solution preparation step (step S1) of preparing a mixed solution containing carbon nanotubes (hereinafter also referred to as "CNTs"), water, and a dispersant for dispersing the CNTs in water, and a CNT dispersion step (step S2) of dispersing the CNTs contained in the mixed solution using a wet atomization device, as shown in Fig. 1. Each step of the method for producing a CNT aqueous dispersion according to this embodiment will be described in order below.

[0019] 1.1. Mixture preparation process (step S1) 1.1.1. Carbon nanotubes (CNTs) The CNTs contained in the mixture produced in the mixture production process include single-walled carbon nanotubes (SWNTs), which are made of a single six-membered ring network (graphene sheet) wound into a cylindrical shape, and multi-walled carbon nanotubes (MWNTs), which are made of multiple graphene sheets wound concentrically. The CNT aqueous dispersion may contain only one of SWNTs and MWNTs, or may contain both. Both ends of the CNTs may be closed or open.

[0020] CNTs are produced by, for example, an arc discharge method, a laser ablation method, a CVD (Chemical Vapor Deposition) method, etc. CNTs are produced to a predetermined size by these methods.

[0021] The diameter of the CNT is, for example, 1 nm or more and 100 nm or less, preferably 5 nm or more and 50 nm or less, and more preferably 8 nm or more and 15 nm or less. If the diameter of the CNT is 1 nm or more and 100 nm or less, the dispersibility of the CNT can be improved. The diameter of the CNT is measured by a SEM (Scanning Electron Microscope).

[0022] The fiber length of the CNT is, for example, 0.5 μm to 50 μm, preferably 15 μm to 35 μm. If the fiber length of the CNT is 0.5 μm to 50 μm, the dispersibility of the CNT can be improved. The fiber length of the CNT is measured by SEM. The "fiber length of the CNT" refers to the length of the CNT in a state where the CNT is bundled by van der Waals forces, and is the length of the CNT before being dispersed in a solvent.

[0023] The BET specific surface area of ​​CNTs is, for example, 50 m 2 / g or more 500m 2 / g or less, preferably 100m 2 / g or more 300m 2 / g or less. The BET specific surface area of ​​the CNT is 50m 2 / g or more 500m 2 / g or less, the dispersibility of CNTs can be improved. Note that the "BET specific surface area" refers to the specific surface area measured by the BET (Brunauer Emmett Teller) method. The BET specific surface area is measured by an automatic specific surface area measuring device.

[0024] In the mixed solution prepared in the mixed solution preparation step, the CNT content is, for example, 1.0% by mass or more and 10.0% by mass or less, preferably 2.0% by mass or more and 8.0% by mass or less, more preferably 2.5% by mass or more and 7.0% by mass or less, even more preferably 3.0% by mass or more and 6.0% by mass or less, and even more preferably 3.5% by mass or more and 5.0% by mass or less. If the CNT content is 2.5% by mass or more, the performance specific to CNT, such as electromagnetic wave shielding performance, can be improved. Furthermore, if the CNT content is 10.0% by mass or less, the dispersibility of CNT can be improved. The CNT content is measured by thermogravimetric analysis (TGA).

[0025] 1.1.2. Dispersants The dispersant contained in the mixture prepared in the mixture preparation step disperses the CNTs in the water solvent. The dispersant is, for example, carboxymethyl cellulose or a salt thereof, or a polymer containing a repeating unit derived from acrylic acid.

[0026] When the dispersant is a salt of carboxymethylcellulose, the substance constituting the salt may be, for example, sodium, lithium, potassium, or ammonium. Among these, the dispersant is preferably sodium carboxymethylcellulose. If the dispersant is sodium carboxymethylcellulose, it can have high solubility in water, which is a solvent.

[0027] When the dispersant is carboxymethyl cellulose or a salt thereof, the etherification degree of the dispersant is, for example, 0.6 to 1.2, and preferably 0.6 to 0.8. If the etherification degree of the dispersant is within the above range, the dispersibility of CNTs can be improved.

[0028] When the dispersant is a polymer containing repeat units derived from acrylic acid, the dispersant is The dispersant is a polymer containing 90% by mass or more, preferably 95% by mass or more, of repeating units derived from acrylic acid. The dispersant may be a copolymer of acrylic acid and 2-acrylamido-2-methylpropanesulfonic acid, or a copolymer of acrylic acid and styrenesulfonic acid. The dispersant may be polyacrylic acid.

[0029] When the dispersant is polyacrylic acid, the dispersibility of CNTs can be improved compared to when the dispersant is sodium carboxymethylcellulose (for details, see "Experimental Examples" described later). Furthermore, when the dispersant is polyacrylic acid, when the CNT aqueous dispersion is applied to a substrate and dried, the adhesion between the substrate and the coating layer containing CNTs can be improved. Examples of substrates include films, papers, and boards.

[0030] The weight average molecular weight of the dispersant is, for example, 5000 to 100000, preferably 10000 to 60000, and more preferably 10000 to 35000. If the molecular weight of the dispersant is 5000 or more, the dispersant is easily entangled with the CNT, and the dispersibility of the CNT is improved. However, if the molecular weight is too large, the dispersibility is deteriorated conversely, so the molecular weight of the dispersant is preferably 100000 or less. The "weight average molecular weight" refers to the weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC).

[0031] In the mixed liquid, the content of the dispersant is, for example, 0.4% by mass or more and 10.0% by mass or less, preferably 0.5% by mass or more and 8.0% by mass or less, and more preferably 1.0% by mass or more and 6.0% by mass or less. If the content of the dispersant is 0.4% by mass or more and 10.0% by mass or less, the dispersibility of the CNTs can be improved. The content of the dispersant is measured by thermogravimetric analysis.

[0032] In the mixture, the mass of CNTs, M CNT Dispersant mass M DISP Ratio of M DISP / M CNT is 1 / 10 or more and 5 or less (CNT:dispersant=10:1 to 1:5), preferably 1 / 5 or more and 4 or less (CNT:CMC=5:1 to 1:4), more preferably 1 / 3 or more and 3 or less (CNT:CMC=3:1 to 1:3), and even more preferably 1 / 2 or more and 1 or less (CNT:CMC=2:1 to 1:1). DISP / M CNT If the ratio M is 1 / 10 or more, the performance specific to CNTs, such as electromagnetic wave shielding performance, can be improved. DISP / M CNT If it is 5 or less, the dispersibility of CNTs can be improved.

[0033] 1.1.3. Water The water contained in the mixed solution produced in the mixed solution production step is used as a solvent. Examples of water include pure water such as ion-exchanged water, ultrafiltered water, reverse osmosis water, and distilled water, as well as water from which ionic impurities have been removed as much as possible, such as ultrapure water. Since the CNT aqueous dispersion uses water as a solvent, it is more environmentally friendly than a case in which an organic solvent is used as a solvent. The CNT aqueous dispersion may contain only CNTs, a dispersant, and water. That is, the CNT aqueous dispersion may be composed of only CNTs, a dispersant, and water.

[0034] 1.1.4. Other additives The mixture prepared in the mixture preparation step may further contain various additives such as a preservative, a pH adjuster, a colorant, and an antifoaming agent, as necessary.

[0035] 1.1.5. Mixing In the mixed liquid preparation step, the CNTs and dispersion liquid as described above are supplied to water, and the CNTs, dispersion liquid, and water are mixed. The mixing is performed, for example, using a homogenizer. The homogenizer may be an ultrasonic type that generates cavitation using ultrasonic waves, an agitation type that agitates the mixed liquid, or a pressure type that applies pressure to the mixed liquid. Homogenizer This treatment can reduce CNT agglomerates, making the CNT dispersion process smoother.

[0036] The viscosity of the mixture, measured using a Brookfield viscometer at 25°C and 60 rpm, is preferably, for example, 50 cps to 3000 cps. If the viscosity of the mixture is within the above range, the mixture can be easily processed using a wet atomizer in the CNT dispersion step. Note that 1 cps = 1 mPa s.

[0037] 1.2. CNT dispersion process (step S2) In the CNT dispersion step, the CNTs contained in the mixed liquid are dispersed using a wet atomization device. Here, Fig. 2 is a cross-sectional view that typically shows the wet atomization device 100 used in the CNT dispersion step.

[0038] As shown in FIG. 2, the wet atomization device 100 includes, for example, a nozzle 10, a collision target member 20, and a housing 30 that houses the nozzle 10 and the collision target member 20.

[0039] The nozzle 10 is coated with, for example, diamond-like carbon (DLC). This can prevent corrosion of the nozzle 10 even if the mixed liquid is acidic. In particular, when the dispersant contained in the mixed liquid is polyacrylic acid, the mixed liquid has strong acidity, so that it is preferable that the nozzle 10 is coated with DLC.

[0040] A nozzle hole 12 is formed in the nozzle 10. Only one nozzle hole 12 is formed in the nozzle 10. Only one nozzle 10 is provided. The nozzle 10 sprays the mixed liquid prepared in the mixed liquid preparation step from the nozzle hole 12.

[0041] The diameter of the nozzle hole 12 formed in the nozzle 10 is, for example, 0.10 mm or more and 0.60 mm or less, and preferably 0.12 mm or more and 0.30 mm or less. If the diameter of the nozzle hole 12 is 0.10 mm or more, clogging of the nozzle hole 12 with the mixed liquid can be suppressed. If the diameter of the nozzle hole 12 is 0.60 mm or less, the collision energy of the mixed liquid can be increased.

[0042] The pressure applied to the mixture sprayed from the nozzle 10 is, for example, 100 MPa to 300 MPa, preferably 150 MPa to 250 MPa. If the pressure is 100 MPa or more, the collision energy of the mixture can be increased. If the pressure is 300 MPa or less, it is possible to prevent the collision energy from being too high, causing the CNT fibers to break and making it impossible to obtain the desired characteristics.

[0043] The processing amount of the mixed liquid sprayed from the nozzle 10 is, for example, 20 L / hr to 400 L / hr, preferably 25 L / hr to 100 L / hr. If the processing amount is 20 L / hr or more, the processing time in the wet type atomization device 100 can be shortened. If the processing amount is 400 L / hr or less, clogging of the nozzle hole 12 with the mixed liquid can be suppressed.

[0044] The collision target member 20 is disposed opposite the nozzle 10. The collision target member 20 is made of, for example, ceramic such as silicon nitride, or metal such as SUS (Steel Use Stainless). In the illustrated example, the collision target member 20 is a ceramic ball. The wet atomization device 100 has a ball collision chamber. The collision target member has, for example, a spherical shape. The collision target member 20 is, for example, eccentric with respect to the nozzle hole 12. This can reduce wear of the collision target member 20.

[0045] In the CNT dispersion process, the mixture is sprayed from a nozzle 10 and made to collide with a collision target 20. The CNTs contained in the mixed liquid are dispersed by shear force when passing through the nozzle hole 12, cavitation due to submerged injection, and impact force when the CNTs collide with the collision target member 20. The dispersed CNTs are discharged from a discharge hole 32 formed in the housing 30. In this way, a CNT aqueous dispersion can be obtained.

[0046] The number of passes of the mixed liquid in the wet atomization device is, for example, 1 to 10 times, preferably 1 to 5 times. If the number of passes is 10 times or less, it is possible to prevent the CNT fibers from being broken due to collision of the mixed liquid, which makes it impossible to obtain the desired characteristics. Furthermore, it is possible to shorten the production time. Furthermore, it is possible to save energy.

[0047] The "number of passes of the mixed liquid in the wet atomization device" refers to the number of times the mixed liquid is circulated in the wet atomization device. For example, "two passes" means that the mixed liquid is circulated twice so that the CNTs that collided once with the collision target member 20 collide with the collision target member 20 again. In this way, the number of passes corresponds to the number of collisions of the mixed liquid sprayed from the nozzle hole 12 with the collision target member 20. The number of passes is proportional to the processing time in the wet atomization device. If the processing time in the wet atomization device is long, the number of circulations of the mixed liquid increases.

[0048] Through the above steps, a CNT aqueous dispersion can be produced.

[0049] 1.3. Purpose The CNT aqueous dispersion produced by the method for producing a CNT aqueous dispersion according to the present embodiment can be applied to, for example, an electromagnetic shielding sheet. For example, the CNT aqueous dispersion can be applied to a substrate, and the applied CNT aqueous dispersion can be dried to obtain an electromagnetic shielding sheet. Examples of methods for applying the CNT aqueous dispersion to a substrate include a method of directly applying the CNT aqueous dispersion to the substrate using a wire bar coater, a knife coater, an air coater, a blade coater, a reverse roll coater, a die coater, a microgravure coater, or the like, and a method of attaching the CNT aqueous dispersion to a roller and transferring the CNT aqueous dispersion attached to the roller to the substrate, such as a so-called roll coater.

[0050] The CNT aqueous dispersion is not limited to an electromagnetic shielding sheet. The CNT aqueous dispersion may be applied to an electromagnetic shielding member that is not in a sheet form. Alternatively, the CNT aqueous dispersion may be applied to a near-infrared cut member or an electric wave absorbing member.

[0051] 1.4. Effects The method for producing a CNT aqueous dispersion according to this embodiment includes a mixed solution preparation step of preparing a mixed solution containing CNTs, water, and a dispersant for dispersing CNTs in water, and a CNT dispersion step of dispersing the CNTs contained in the mixed solution using a wet atomization device 100. In the CNT dispersion step, the mixed solution is sprayed from a nozzle 10 of the wet atomization device 100 and collided with a ceramic or metallic collision target member 20. Therefore, a CNT dispersion with better dispersibility can be produced compared to, for example, a case where mixed solutions containing CNTs are collided with each other (for details, see "Experimental Examples" described later).

[0052] In the manufacturing method of the CNT aqueous dispersion according to this embodiment, the collision target member 20 may be a ceramic ball. If the collision target member 20 is a ceramic ball, the mixed liquid can be smoothly discharged to the discharge hole 32 while increasing the collision energy.

[0053] In the method for producing a CNT aqueous dispersion according to this embodiment, the dispersant may be carboxymethyl cellulose or a salt thereof, or a polymer containing a repeating unit derived from acrylic acid. If the polymer contains repeating units derived from this, it is possible to produce a CNT aqueous dispersion with good dispersibility.

[0054] In the method for producing a CNT aqueous dispersion according to this embodiment, the dispersant may be sodium carboxymethylcellulose. If the dispersant is sodium carboxymethylcellulose, a CNT aqueous dispersion with good dispersibility can be produced.

[0055] In the method for producing a CNT aqueous dispersion according to this embodiment, the dispersant may be polyacrylic acid. If the dispersant is polyacrylic acid, a CNT aqueous dispersion with better dispersibility can be produced compared to a case where the dispersant is, for example, sodium carboxymethylcellulose.

[0056] In the method for producing a CNT aqueous dispersion according to this embodiment, the CNT content in the mixed solution may be 2.0% by mass or more, 3.0% by mass or more, or 3.5% by mass or more. In the method for producing a CNT aqueous dispersion according to this embodiment, the mixed solution is sprayed from the nozzle 10 of the wet atomization device 100 and collided with the ceramic or metallic collided member 20, so that a CNT aqueous dispersion with good dispersibility can be produced even if the CNT content is 2.0% by mass or more, 3.0% by mass or more, or 3.5% by mass or more.

[0057] 2. Experimental Example The present invention will be described in more detail below with reference to the following experimental examples, but the present invention is not limited to these experimental examples.

[0058] 2.1. Preparation of the mixture 2.1.1. Examples 1 to 3 FIG. 3 is a table showing the preparation conditions of the mixed liquids of Examples 1 to 3, and Examples 4 to 10 and Comparative Examples 1 to 8 described below.

[0059] A mixed solution was prepared by mixing CNT, a dispersant, and water. A homogenizer "Biomixer BM-2" manufactured by Nippon Seiki Seisakusho Co., Ltd. was used for mixing. The mixing time was 5 minutes.

[0060] The CNT used was "K-Nanos-100P" manufactured by Kumho Petrochemical Co., Ltd. The CNT was MWCNT, with a diameter of 8 nm to 15 nm, a fiber length of 27 μm (bundle), and a BET specific surface area of ​​220 m 2 The CNT content (concentration) in the mixed liquid was varied within the range of 2.0% by mass to 3.0% by mass.

[0061] Sodium carboxymethylcellulose was used as the dispersant. Specifically, "Cellogen 5A" manufactured by Daiichi Kogyo Seiyaku Co., Ltd. was used as the sodium carboxymethylcellulose. The weight average molecular weight was 13,000. The degree of etherification was 0.7. The concentration of the dispersant in the mixed liquid was varied in the range of 2.0% by mass to 3.0% by mass. In FIG. 3, "Cellogen 5A" is represented as "CMC1."

[0062] Next, the CNTs contained in the mixed liquid were dispersed in the mixed liquid using a wet atomization device having a ball collision chamber. The wet atomization device used was a wet atomization device "Starburst Lab" (model name: HJP-25005) manufactured by Sugino Machine Co., Ltd. The diameter of the nozzle hole from which the mixed liquid was sprayed was set to 0.17 mm, and the pressure applied to the mixed liquid was set to 200 MPa. The processing amount of the mixed liquid was 47 L / hr. The mixed liquid was collided with ceramic balls. The number of passes of the mixed liquid through the wet atomization device was shaken in the range of 1 to 3 times. In this manner, a CNT aqueous dispersion containing CNTs, a dispersant, and water was produced.

[0063] Example 4 Example 4 is the same as Example 1, except that "Cellogen WS-C" manufactured by Daiichi Kogyo Seiyaku Co., Ltd. was used as sodium carboxymethylcellulose. "Cellogen WS-C" has a higher viscosity than "Cellogen 5A". In FIG. 4, "Cellogen WS-C" is written as "CMC2".

[0064] 2.1.3. Examples 5 to 9 Examples 5 to 9 are similar to Example 1 described above, except that polyacrylic acid was used as the dispersant, and the concentrations of CNT and dispersant in the mixed solution were varied in the range of 2.0% by mass to 4.0% by mass. Specifically, "AQUALIC HL-415" manufactured by Nippon Shokubai Co., Ltd. was used as the polyacrylic acid. The weight average molecular weight was 10,000. In FIG. 3, "AQUALIC HL-415" is written as "PAA."

[0065] Example 10 Example 10 is the same as Example 1 described above, except that a copolymer of acrylic acid and 2-acrylamido-2-methylpropanesulfonic acid was used as the dispersant. Specifically, "Aron A-12SL" manufactured by Toa Gosei Co., Ltd. was used as the copolymer of acrylic acid and 2-acrylamido-2-methylpropanesulfonic acid. The weight average molecular weight was 10,000. In FIG. 3, the copolymer of acrylic acid and 2-acrylamido-2-methylpropanesulfonic acid is indicated as "PAA / PSA."

[0066] 2.1.5. Comparative Examples 1 to 3 In Comparative Example 1, the mixed solution of Example 1 was treated using a wet-type atomizer having an oblique collision chamber instead of a ball collision chamber. In Comparative Examples 2 and 3, the concentrations of CNT and dispersant were varied.

[0067] In a wet atomization device having an oblique collision chamber, a mixed liquid containing CNTs is sprayed at high pressure from a pair of nozzle holes (a first nozzle hole and a second nozzle hole), and the mixed liquid sprayed from the first nozzle hole and the mixed liquid sprayed from the second nozzle hole are collided with each other to disperse the CNTs. The central axis of the first nozzle hole and the central axis of the second nozzle hole are not in a straight line but are inclined to each other.

[0068] The diameter of the pair of nozzle holes from which the mixed liquid is discharged is set to 0.12 mm, and the pressure applied to the mixed liquid is set to 200 MPa. The processing amount of the mixed liquid is 47 L / hr. By setting the diameter of the pair of nozzle holes to 0.12 mm, the total cross-sectional area of ​​the two nozzle holes of the wet atomization device having an oblique collision chamber of Comparative Example 1 can be made the same as the cross-sectional area of ​​one nozzle hole of the wet atomization device having a ball collision chamber of Example 1. This allows the processing amounts of both to be the same.

[0069] 2.1.6. Comparative Examples 4 to 6 Comparative Examples 4 to 6 were the same as Comparative Example 1 described above, except that "Cellogen WS-C" manufactured by Daiichi Kogyo Seiyaku Co., Ltd. was used as the sodium carboxymethylcellulose.

[0070] 2.1.7. Comparative Examples 7 and 8 Comparative Examples 4 to 6 were similar to the above-mentioned Comparative Example 1, except that polyacrylic acid was used as the dispersant. Specifically, "AQUALIC HL-415" manufactured by Nippon Shokubai Co., Ltd. was used as the polyacrylic acid.

[0071] Experimental Method By measuring the median diameter of the CNTs contained in the mixture prepared as above, The dispersibility of CNTs was evaluated. The median diameter of CNTs was measured using a laser diffraction / scattering particle size distribution analyzer "LA-960V2" manufactured by Horiba, Ltd. The smaller the median diameter of CNTs, the better the dispersibility of CNTs.

[0072] Furthermore, the pH of the mixed solution was measured using a "desktop pH meter" manufactured by Horiba, Ltd. under conditions of 25°C and 1 atm.

[0073] 2.3. Experimental Results The median diameter and pH of the mixed liquids of Examples 1 to 10 and Comparative Examples 1 to 3 are shown in FIG.

[0074] As shown in Fig. 3, in Examples 1 to 10 in which a ball collision chamber was used, the median diameter was smaller than in Comparative Examples 1 to 3 in which an oblique collision chamber was used. Specifically, a comparison between Example 1 and Comparative Example 1, Example 4 and Comparative Example 4, and Example 5 and Comparative Example 7 in which the CNT concentration and the type and concentration of the dispersant were the same showed that the median diameter was smaller when the oblique collision chamber was used. Therefore, it was found that the dispersibility was better when the ball collision chamber was used than when the oblique collision chamber was used.

[0075] When an oblique collision chamber was used, the nozzle hole became clogged when the CNT concentration was 2.5 mass% or more, and processing by the wet atomization device was not possible. In other words, the CNTs could not be dispersed by the wet atomization device. On the other hand, when a ball collision chamber was used, processing by the wet atomization device was possible even when the CNT concentration was 2.5 mass% or more.

[0076] In addition, by comparing Examples 1 to 4 with Examples 5 to 7, the median diameter was smaller when polyacrylic acid was used as a dispersant than when sodium carboxymethylcellulose was used, and therefore it was found that the dispersibility was better when polyacrylic acid was used as a dispersant than when sodium carboxymethylcellulose was used.

[0077] The above-described embodiment and modifications are merely examples, and the present invention is not limited to these. For example, the embodiments and modifications can be appropriately combined.

[0078] The present invention is not limited to the above-described embodiment, and various modifications are possible. For example, the present invention includes a configuration that is substantially the same as the configuration described in the embodiment. A substantially identical configuration is, for example, a configuration that has the same function, method, and result, or a configuration that has the same purpose and effect. The present invention also includes a configuration in which non-essential parts of the configuration described in the embodiment are replaced. The present invention also includes a configuration that has the same action and effect as the configuration described in the embodiment, or a configuration that can achieve the same purpose. The present invention also includes a configuration in which publicly known technology is added to the configuration described in the embodiment. [Explanation of symbols]

[0079] 10... nozzle, 12... nozzle hole, 20... collision target member, 30... housing, 32... discharge hole, 100... wet atomization device

Claims

1. A step of preparing a mixed liquid including carbon nanotubes, water, and a dispersant for dispersing the carbon nanotubes in the water; dispersing the carbon nanotubes contained in the mixture using a wet atomization device; Including, In the step of dispersing the carbon nanotubes, the mixed liquid is sprayed from a nozzle of the wet-type atomization device and collided with a ceramic or metallic collision target member, in accordance with the method for producing a carbon nanotube aqueous dispersion.

2. The method for producing a carbon nanotube aqueous dispersion according to claim 1 , wherein the collision target is a ceramic ball.

3. 3. The method for producing a carbon nanotube aqueous dispersion according to claim 1, wherein the dispersant is carboxymethyl cellulose or a salt thereof, or a polymer containing a repeating unit derived from acrylic acid.

4. The method for producing a carbon nanotube aqueous dispersion according to claim 3 , wherein the dispersant is sodium carboxymethylcellulose.

5. The method for producing a carbon nanotube aqueous dispersion according to claim 3 , wherein the dispersant is polyacrylic acid.

6. The method for producing a carbon nanotube aqueous dispersion according to claim 1 , wherein the content of the carbon nanotubes in the mixed liquid is 2.0% by mass or more.

7. The method for producing a carbon nanotube aqueous dispersion according to claim 1 , wherein the content of the carbon nanotubes in the mixed liquid is 3.0% by mass or more.

8. The method for producing a carbon nanotube aqueous dispersion according to claim 5 , wherein the content of the carbon nanotubes in the mixed liquid is 3.5% by mass or more.

Citation Information

Patent Citations

  • Method for manufacturing carbon nanotube aqueous dispersion

    WO2021065432A1